Pd loaded spider-web TiO2 nanowires: Fabrication, characterization and gas sensing properties - Sennik, Erdem; Soysal, Ugur; Ozturk, Zafer Ziya (Elsevier Science Sa, 2014)
Pd loaded spider-web TiO2 nanowires were fabricated using Ti foil to sense volatile organic compound (VOC). The spider-web TiO2 nanowires on Ti foil were synthesized in an aqueous 1 M sodium hydroxide (NaOH) solution at 220 degrees C by hydrothermal method. In order to load palladium the spider-web TiO2 nanowires and palladium (II) acetate [Pd(OAc)(2)] powder were placed at a certain distance in a quartz boat inside a furnace for a thermal process. The samples were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS) techniques. VOC gas sensing properties of the spider-web nanowires have been investigated in the concentration range of 500-5000 ppm at 200 degrees C. The results show that the sensor response for Pd loaded spider-web TiO2 nanowires increase depending on the increments of the VOC concentration. The maximum sensor response was obtained for isopropyl alcohol. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Metal oxide nanowire; TiO2; Hydrothermal method; Pd loaded; VOC; Gas sensor